COVID-19 impact on junior doctor education and training: a scoping review. Issue 1160 (9th March 2021) - Seifman, Marc Adam; Fuzzard, Sibon K; To, Henry; Nestel, Debra
Abstract: COVID-19 has had a significant impact on healthcare resources and the medical workforce. Clinically-based medical education is the principal source of learning, and this has been profoundly impacted by restrictions due to COVID-19. It follows that junior medical staff and their education would be significantly impacted due to the altered volume and breadth of their clinical exposure. Some literature has been published regarding the impact to medical training during COVID-19. This study sought to review junior medical staff perceptions and their reported impact of the COVID-19 pandemic on their education and training. Nine databases (three Ovid MEDLINE databases, Embase, Web of Science, Scopus, Cumulative Index to Nursing and Allied Health Literature, Educational Resources Information Centre and PsychINFO) were searched for studies published in 1 January 2020 through 24 August 2020. Via a scoping review protocol, an iterative process was used to perform the identification, review and charting analysis of the reported outcomes and themes. Descriptive analysis was performed using quantitative and qualitative methods. Of the 25 343 sources identified, 32 were included in the review. There were studies published from nearly all continents, predominantly in surgical journals, with a wide spread of specialties. Themes identified included the current impact of the pandemic in relation to continuation of and modifications to training programmes, as well as the future impact due to training requirements and career progression. Junior medical staff report that the COVID-19 pandemic has had a significant impact on their education and training. Whether the changes imposed by the pandemic on education are temporary measures or permanent fixtures, and whether standards of competence may be impacted, is not yet known. This scoping review forms a basis for further investigation in the field.